Nilai Perusahaan: Kontribusi Penerapan Akuntansi Manajemen Lingkungan Pada Perusahaan Industri Manufaktur di Banten - Bahtiar Effendi (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2021)
This study aims to analyze the factors of environmental management reporting on firm value in Banten. The population of this study were all manufacturing companies located in Banten in the 2019-2020 period, totaling 2,579 companies. Determination of the selected sample based on purposive sampling criteria with quantitative approach method. This study uses primary data obtained from answers to questions through questionnaires given to respondents and secondary data from company financial reports. By using multiple linear regression as a research method, it is found that there is a significant influence between aspects of transportation on firm value. Furthermore, it is also found that the results of other aspects have a significant positive effect on firm value. However, there are four aspects of the proxies for the application of environmental management accounting which consist of material input aspects, non-product output aspects, compliance aspects and supplier assessment aspects that have a positive but insignificant effect on firm value. Finally, the environmental complaint mechanism aspect has a negative but insignificant effect on firm value. Agency theory and signaling theory were successfully applied in this study, the variables of environmental management accounting application represented by material input aspects, non-product output aspects, compliance aspects, transportation aspects, other aspects, supplier assessment and environmental complaint mechanisms were proven to simultaneously affect firm value.